Microorganism as plastic biodegradation agent towards sustainable environment - Wan Muhamad, Wan Naimatul Asiah; Othman, Rashidi; Shaharuddin, Ruhul Izzati; Hasni, Mohd Shah Irani (2015)
The usage of plastic is critically in demand due to its character which can be shaped into almost any desired shape and its ability to retain that shape. Unfortunately, the wastage of those plastics leads to many environmental issues and hazards towards human health. Basically, plastics can degrade in the environment through four mechanisms which are photodegradation, thermooxidative, hydrolytic degradation and microbial degradation. Microbial degradation is subject to microorganism which acts as biodegradation agent. In this case, microorganism will secrete an active enzyme to break down long chain polymers. Microbial enzymes are attractive because the cost to grow and maintain them is less and they are easy to manipulate. Rhizopus delemar , Rhizophus arrizus and Pseudomonas sp. were among the most cited bacteria that have successfully degraded certain type of plastics. Whereas, fungal species of Aspergillus flavus and Penicillium funiculosum were recorded by scientist which react with certain plastic’s substrate. The objective of this paper is to review several species of microorganism that have been experimented by scientist and were claimed to have the capability to degrade plastic towards eco-friendly approaches in order to sustain our environment. In conclusion, microorganisms are very effective agent to fasten degradation process of plastics without causing any side effect like chemical or synthetic method does.